2019
DOI: 10.1080/08870446.2019.1652752
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ interpretations of e-cigarette advertising and their engagement with e-cigarette information: results from five focus groups

Abstract: Objective: The objective of this study is to explore adolescent non-ecigarette users' interpretations of e-cigarette advertising and their engagement with e-cigarette information. Given adolescents' lack of persuasion knowledge and the association between advertising and behaviour, insights from non-users who are heavily targeted by the industry add evidence to a field that mainly focuses on risk perceptions and reasons for experimentation. Design: Five focus groups were conducted with 39 adolescents (mean = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…The most highly cited reasons were most prominent in the ads, including a focus on relational aspects of vaping and product-related benefits, such as a positive sensory experience. Similar to the findings of the present study, a recently published focus group study that analyzed e-cigarette advertisements with 39 non-vaping adolescents found that the perceived social benefits, like increased friendships, and product-related appeals, like the innovative design and variety of flavors, presented in the advertisements were major draws to trying e-cigarettes [ 37 ]. The present study builds on these findings even further and adds to a growing evidence base that adolescents are indeed the target market for e-cigarette advertisers, despite claims that this is not the case.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The most highly cited reasons were most prominent in the ads, including a focus on relational aspects of vaping and product-related benefits, such as a positive sensory experience. Similar to the findings of the present study, a recently published focus group study that analyzed e-cigarette advertisements with 39 non-vaping adolescents found that the perceived social benefits, like increased friendships, and product-related appeals, like the innovative design and variety of flavors, presented in the advertisements were major draws to trying e-cigarettes [ 37 ]. The present study builds on these findings even further and adds to a growing evidence base that adolescents are indeed the target market for e-cigarette advertisers, despite claims that this is not the case.…”
Section: Discussionsupporting
confidence: 84%
“…Adolescence is a period of psychosocial development where it is more likely that an individual will engage in sensation seeking than at other developmental stage [ 63 ]. Other researchers confirm that e-cigarette advertisements capitalize on this sensation-seeking behavior by emphasizing pleasurable sensations, such as flavors or odor produced by the e-juice [ 37 , 64 - 66 ]. The advertisements reinforce the belief that e-cigarettes will satisfy the sensation-seeking needs of youth by highlighting the sensory experience that comes with e-cigarette use in their animations, graphics, and music.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high likelihood for nicotine dependence following e-cigarette use, youth are unlikely to view use as risky (Amrock et al 2016 ; Chen et al 2020 ). It remains critical to prevent adolescent use of e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Content analyses have determined that the widespread misinformation related to e-cigarettes on the internet, largely sponsored by marketers (Collins et al, 2019), often advertises e-cigarettes as a “reduced risk cigarette” and as a smoking cessation aid (Chen et al, 2020). Such misinformation promotes the image that e-cigarettes are healthier, more socially acceptable, and more environmentally friendly.…”
mentioning
confidence: 99%
“…Such misinformation promotes the image that e-cigarettes are healthier, more socially acceptable, and more environmentally friendly. It has perpetuated the misperceptions that e-cigarettes are risk free, not addictive, do not contain toxic chemicals, and can help people quit smoking (Chen et al, 2020; Collins et al, 2019). The misleading information has a particularly strong influence on those who have never smoked and young people without much knowledge of persuasion tactics (Chen et al, 2020).…”
mentioning
confidence: 99%